Isolation and Screening of Aspergillus niger and Bacillus coagulans as Potential Candidates for Amylase and Glucose Isomerase Production - Musa, B.; Zangina, B. U.; Ado, S. A.; Hussaini, I. M.; Madika, A.; Aliyu, M. S. (UMYU Journal of Microbiology Research)
There is an increasing demand for high fructose corn syrup as an alternative to glucose especially for use by people with diabetes due to its low glycemic index. The high cost of this product coupled with its high demand has attracted the attention of many researchers to search for an alternative and sustainable production route. Therefore, the focus of this work was isolating and screening Aspergillus niger and Bacillus coagulans as possible producers of amylase and glucose isomerase respectively, which are needed to produce high fructose corn syrup. Nine (9) samples of loamy soil were taken from three (3) separate locations (BG = Botanical Garden, RD = Refuse Dumpsite, FB = Flower Bed) to isolate the bacterium and fungus. Based on the lacto-phenol cotton blue stain preparation under a microscope, colonies that were thought to be Aspergillus niger colonies were observed and further identified. Cultural, microscopic, and biochemical characteristics were used to confirm the identification of colonies that were thought to be Bacillus coagulans. The probable isolates of Aspergillus niger and Bacillus coagulans were then screened for amylase and glucose isomerase production respectively. Out of the total of nine (9) soil samples analysed, 5 (55.6 %) were positive for Aspergillus niger. A higher isolation rate of Aspergillus niger, 2 (66.7 %) was recorded in soil samples from botanical garden (BG) and flower bed (FB). The lowest isolation rate, 1 (33.3 %) was observed in soil obtained from the refuse dump. Out of all the isolates screened for their potential to produce amylase, the isolate from the botanical garden showed the highest zone of starch hydrolysis (28 mm), and the isolate from the flower bed showed the least zone of hydrolysis of starch (13 mm). On the other hand, out of the nine (9) soil samples analysed, 6 (66.7 %) were positive for Bacillus coagulans and the highest occurrence of Bacillus coagulans, 3 (100 %) was recorded with soil from botanical garden (BG1), while the least occurrence, 1 (33.3 %) was observed in soil from flower bed (FB2). The probable isolates of Bacillus coagulans screened for glucose isomerase production revealed that all the six (6) isolates produced glucose isomerase, with isolate from refuse dump (RD2) producing the highest concentration of glucose isomerase (4.7014 g/L).